(untitled) (Research, Society and Development, 2022)
In the present study, we described the phenology and characteristics of two upland rice varieties, namely Cana Roxa and Mato Grosso. The experiments were conducted at the College of Agricultural Science (Faculdade de Ciências Agrárias; FCA) of the State University of Piauí (Universidade Estadual do Piauí; UESPI), Parnaíba, State of Piauí, Brazil. The variety trial comprised six plots measuring 5 m × 4 m, and each linear meter was planted with 10 g seeds. Three rounds of NPK fertilization were applied to establish the plants and realize the subsequent cultural practices, such as weeding and sprinkler irrigation. The germination rate, number of plants per linear meter, plant height, booting stage, blooming stage, harvest, and morpho-agronomic descriptors were evaluated. Cana Roxa reached the tillering, booting, blooming, fructification, and maturation stages at 7, 66, 77, 86, and 108 days after sowing (DAS), respectively, indicating that it is a medium-duration variety with a 114-day cycle. Mato Grosso reached the tillering, booting, blooming, fructification, and maturation stages at 5, 59, 72, 88, and 107 DAS, respectively, indicating that it is an early-duration variety with a 110-day cycle. Both genotypes lacked lodging and produced long grains, grains with golden husks, white grains, straw-yellow lemmas, and panicles with an intermediate shape.